Progress from Forecast Failure - the Norwegian Consumption Function - Øyvind Eitrheim; Eilev S. Jansen; Ragnar Nymoen (Norges Bank, 2000)
After a forecast failure, a respecification is usually necessary to account for the data ex post, in which case there is a gain in knowledge as a result of the forecast failure. Using Norwegian consumption as an example, we show that the financial deregulation in the mid 1980s led to forecast failure both for consumption functions and Euler equations. Counter to wideheld beliefs, we show analytically and empirically that this constellation of forecast failures is inconsistent with an underlying Euler equation. Instead, respecification led to a new consumption function where wealth plays a central role. That model is updated and is shown to have constant parameters despite huge changes in the income to wealth ratio over nine years of new data.
hdl:11250/2500398
Keywords: C51; C52; C53; E21; E27; 330; VAR models; Euler equations; consumption functions; equilibrium correction models; financial deregulation; forecast failure; progressive research strategies